Sosialisasi Pengembangan Kompetensi SDM Jurusan Tata Busana dalam Menghadapi Industri Fashion Teknologi Digital di SMK Al Ihsan - Aldi Al Fauzi; Hanifah Efi Rahayu; Muhammad Bagus Pratama; Namira Ayu Arini Putri; Unna Ria Safitri (Bumi: Jurnal Hasil Kegiatan Sosialisasi Pengabdian kepada Masyarakat, 2026)
This community service activity aims to socialize the development of Human Resource (HR) competencies in the Fashion Design Department at SMK Al Ihsan to face the transformation of the fashion industry based on digital technology. The main challenge faced is the gap (mismatch) between the school curriculum, which still focuses on conventional production techniques, and the needs of an industry that is now digital and automated. The method used in this activity is a participatory and educational approach that includes four stages: needs observation, delivery of theoretical material (lecturing), focused group discussions (FGD) accompanied by application demonstrations, and evaluation. The results of the activity show an increase in participants' understanding of concepts such as eco-fashion, the creative economy, as well as the introduction of digital technologies like 3D design applications (CLO3D) and digital pattern making. Through the integration of four competency pillars hard skills, soft skills, digital skills, and entrepreneurial skills it is expected that graduate profiles can transform from operational seamstresses into competitive fashionpreneurs in the global market. The conclusion of this activity emphasizes that the Link and Match strategy and mastery of technological literacy are key to effectively reducing the skills gap of students in the Industry 4.0 era.